การใช้รูปแบบการสอนเขียนแบบเน้นกระบวนการเพื่อพัฒนาความสามารถ ด้านการเขียนภาษาอังกฤษของนักเรียนชั้นประถมศึกษาปีที่ 5 - ภัทรลดา วงษ์โยธา, อัญชลีพร คำมงคล, (วารสารวิชาการพระพุทธศาสนาเขตลุ่มน้ำโขง, 2019)
The purposes of this study were to study and compare English writing ability using the model of writing’s process of Prathomsuksa 5 students before and after the instruction, and to study students’ attitude towards teaching English writing using the model of writing’s process. The sample consisted of 10 students of second year students at Ban SoksiewSaensuk School, Khonkaen Province, in the first semester of the academic year 2017. They were selected by cluster random sampling. The design of this research was a one group pretest-posttest design. The research instruments included 10 lesson plans, an English writing ability test, and an attitude questionnaire. The findings were as follows; 1.The students’ pretest and posttest mean scores on English writing ability were 12.00 or 40.00 percentand 23.00or 76.67percent respectively. The posttest score was higher than the criteria of 70 percent and it was significantly higher than that of the pretest at the .01 level. 2.The students’ attitude towards teaching English writing using role the model of writing’s process was at a good level. Keywords: The model of writing’s process, writing ability, the students’ attitudes